UV-Protection Activities of Labu Siam (Sechium edule) Extract Based on Sun Protection Factor (SPF) - Anggraeni, Bella; Aminah, Aminah; Fawwaz, Muammar (Universitas Muslim Indonesia, 2024)
Exposure to sunlight has a negative effect on the skin. Sunscreens are used to protect the skin from the harmful effects caused by UV radiation. The ability of a sunscreen to protect the skin by delaying erythema is expressed by the value of the Sun Protection Factor (SPF). The purpose of this study was to analyze the UV protection activity of chayote (Sechium edule) based on the Sun Protection Factor (SPF) value, which was measured using UV-Vis spectrophotometry and calculated using the Mansyur equation. Based on the results of the study, it can be concluded that the SPF value of chayote (Sechium edule) extract has UV protection activity. At concentrations of 1%, 2%, and 3% there is activity as UV protection with SPF values of 7.487; 11.817; and 16,889. From the results obtained, it can be seen that the higher the concentration, the greater the SPF value obtained.UV-Protection Activities of Labu Siam (Sechium edule) Extract Based on Sun Protection Factor (SPF)